The Anterior Cruciate Ligament (ACL) Is Extensively Studied Due to Its Anatomical Position and Its Role In Preventing Anterior Tibial Translation and Rotational Stresses At The Knee Joint - Lakshmipriya Jeyanthi (Multidisciplinary Journal of Akseprin Indonesia, 2024)
ACL injuries predominantly arise in sports, typically resulting from twisting or pivoting actions. Reduced range of motion, along with diminished muscle strength and functional capacity, is more prevalent in persons who have undergone ACL reconstruction. Russian current is an innovative modality in musculoskeletal physiotherapy. Objective: To evaluate the impact of Russian current combined with structured exercise on enhancing knee function post-ACL surgery. Methodology: This study had 44 patients who underwent ACL reconstructions. They were randomly assigned to Group A (n=22), which received organized exercise alone, and Group B (n=22), which received Russian current in conjunction with structured exercise over a duration of 6 weeks. The knee's range of motion, isometric muscular strength, and function were evaluated using a universal goniometer, a handheld dynamometer, and Lysholm knee scores, respectively. The evaluation was conducted six weeks post-treatment. The intergroup comparison was conducted using an unpaired t-test, revealing statistically significant improvements (p<0.00) in knee flexion (t=29.41), extension range (t=2.08), isometric quadriceps strength (t=10.04), hamstring muscle strength (t=17.81), and functional status (t=13.74) in the group that received Russian current in conjunction with structured exercises, as opposed to those who received structured exercises alone. Conclusion: The findings indicate that Russian current, in conjunction with structured exercise, significantly enhanced knee range of motion, muscle strength, and functional status in individuals with ACL repair compared to structured exercise alone